(untitled) - Huỳnh, Thiện Chí (Cần Thơ, 2020)
Speaking is one of the most important skills in learning and teaching English as a foreign language (EFL), but a problem commonly found in English speaking classes is students‘ low participation that is a barrier in teachers‘ plans. Therefore, this study was conducted to investigate students‘ perceptions of factors influencing students‘ low participation in English speaking classes and strategies to promote students‘ participation. The research was conducted on 206 participants from a high school in the Mekong Delta. Two research instruments were employed including questionnaires and semi-structure interview. The results from the study revealed that students‘ perceptions of factors influencing students‘ low participation in English speaking classes were medium. Especially, the results showed that students‘ low participation in English speaking classes was strongly influenced by students‘ factors such as English proficiency level and psychology, and was least affected by teachers‘ factors, as teaching methods and teacher‘s roles in speaking activities. The results also indicated that students‘ perceptions of strategies to promote students‘ participation in English speaking classes were high. Additionally, strategies such as establishing a supportive and caring relationship with students, creating a pleasant classroom climate, making tasks stimulating and presenting them properly, promoting students‘ self-confidence were often employed by teachers to increase students‘ participation. The results of the study were expected to contribute to the comprehension of teachers‘ strategies to enhance students‘ participation in English speaking classes.
Keywords: English language,Anh ngữ; Study and teaching,Dạy và học